THE ROLE OF FAIRY TALES IN BUILDING THE CHARACTERS AND SCIENTIFIC ATTITUDE - Ninuk Lustyantie (International Conference on Languages and Arts, 2014)
In the process of life, we had made human beings as the subject of education. In that process, a person learns and understands of the others’ character, nature, feeling, and the way of thinking. Character is defined as a way of thinking and behaving that is typical of each individual to live and work together, both within the family, community, nation, and state that shows how a person behaves. The process of character formation is mainly directed to students. Fairy tale can be used as a tool or a bridge to achieve the mission and vision of character education. Before the society is familiar with writing, the fairy tales were used as media of social values and very in teaching from one generation to another generation. In addition to being used to sharpen the students’ fantasy and imagination, telling a fairy tale is a very effective method of delivering messages to the learners. Moreover, the activities of storytelling are also the best tool in the process of refreshing the tense atmosphere back to the pleasant atmosphere. Understanding and cultivation of character education through the fairy tale will be more easily applied by learners in daily life through the study of literature which is also expected to establish a scientific attitude.   Keywords: fairy tale, character education, scientific attitude